2019
DOI: 10.1084/jem.20191155
|View full text |Cite
|
Sign up to set email alerts
|

Extensive dissemination and intraclonal maturation of HIV Env vaccine-induced B cell responses

Abstract: Well-ordered HIV-1 envelope glycoprotein (Env) trimers are prioritized for clinical evaluation, and there is a need for an improved understanding about how elicited B cell responses evolve following immunization. To accomplish this, we prime-boosted rhesus macaques with clade C NFL trimers and identified 180 unique Ab lineages from ∼1,000 single-sorted Env-specific memory B cells. We traced all lineages in high-throughput heavy chain (HC) repertoire (Rep-seq) data generated from multiple immune compartments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 55 publications
6
31
3
Order By: Relevance
“…Using the germline database reported in this study, we were able to assign vaccine-elicited antibody sequences to specific germline genes/alleles and determine levels of SHM much more accurately. The average levels of SHM reported in this study (6.3% for HC and 4.2% for LC) are comparable to the average levels of SHM reported in similar immunization studies where per animal germline BCR databases were inferred using IgDiscover [47,48]. Our germline database provides a resource for assigning germline genes/alleles and accurately calculating rates of SHM when inferring individual germline databases for each animal is logistically impractical.…”
Section: Plos Pathogenssupporting
confidence: 71%
“…Using the germline database reported in this study, we were able to assign vaccine-elicited antibody sequences to specific germline genes/alleles and determine levels of SHM much more accurately. The average levels of SHM reported in this study (6.3% for HC and 4.2% for LC) are comparable to the average levels of SHM reported in similar immunization studies where per animal germline BCR databases were inferred using IgDiscover [47,48]. Our germline database provides a resource for assigning germline genes/alleles and accurately calculating rates of SHM when inferring individual germline databases for each animal is logistically impractical.…”
Section: Plos Pathogenssupporting
confidence: 71%
“…Similar to the D11A antibodies, D15.SD7, D19.PA8, and VD20.5A4 bind mostly the V2 hypervariable region. They bury ~ 878 Å 2 , ~790 Å 2 and ~522 Å 2 of the V1V2, respectively (Fig 2D-G) of which ~781 Å 2 , 182~579 Å 2 and ~4 80 Å 2 are in the V2 region only.In conclusion, the structural analyses support our previous alanine scanning results, which showed that Glu 185 , Glu 186 , Glu 186A , Arg 186B , and Lys 186C mutations resulted in decrease or loss of neutralizing activities of D11A.F2 and GM9_TH8[25,26]. Indeed, all mAbs interact with the above-mentioned V2 residues (Fig2, S2-6 Tables).…”
supporting
confidence: 86%
“…Tables), with the light chains of D15.SD7 and D19.PA8 showing some contacts with the proximal N-acetylglucosamine (NAG) at residue N187 (Fig2D and 2E). We could not explain the slight difference in specificity at residues Pro 183 and Leu 184 described previously(Phad et al, 2020).Finally, we also note that D15.SD7, D19.PA8 and VD20.5A4 all contact Lys 155 in strand B as well as make additional contacts with the scaffolded V1V2 outside of V2 (Fig2).Since our high-resolution structures were solved with V2 peptide or V1V2 domain, we superimposed the above-described structures of mAb/V2b or V1V2 onto the structure of the 16055 NFL trimer (PDB ID: 5UM8)[19] by aligning the V2 or V1V2 region (S2 Fig).We observed that some mAbs showed additional contacts to the trimer not observed in our structures, either because the residues were not present in the V2 peptide and V1V2 domains or because these residues were disordered or did not show interactions in the solved structure (S2 Fig). Interestingly, in the superposition, mAb VD20.5A4 did not show additional contacts to the 16055 NFL trimer.…”
contrasting
confidence: 70%
See 2 more Smart Citations